Preoperative Significance of Ipsilateral Manual Neck Compression in Patients With Pulsatile Tinnitus Secondary to Sigmoid Sinus Dehiscences and Diverticula - Lee, Seung Jae; Lee, Sang-Yeon; Choi, Byung Yoon; Koo, Ja-Won; Hong, Sung Hwa; Song, Jae-Jin (Frontiers in Neurology, 2022)
Venous pulsatile tinnitus (PT) is characterized by an auditory perception of pulse-synchronous sound, suppressed by compression of the ipsilateral internal jugular vein. We sought to determine the preoperative prognostic significance of the effect of ipsilateral neck manual compression on the PT loudness and audiometric changes in patients with sigmoid sinus dehiscences (SS-Deh) and diverticula (SS-Div) by comparing postoperative improvements in ipsilateral low-frequency hearing loss (LFHL) in pure-tone audiogram (PTA) and PT symptoms. Twenty-two subjects with PT originating from SS-Deh/Div were recruited. Air-conduction hearing thresholds were measured using PTA at three time points: twice preoperatively (with neutral neck position and with ipsilateral manual compression of internal jugular vein) and once at 3-months postoperatively with neutral neck position. We defined a positive neck compression effect as a threshold improvement of ≥ 10 dB HL at 250 or 500 Hz after manual neck compression. All but two subjects presented with ipsilateral LFHL in the neutral position. The average hearing threshold in the neutral position markedly improved after manual neck compression, indicating that LFHL originated from the masking effect of venous PT. All subjects had subjective improvements in PT and LFHL after sigmoid sinus surgeries, confirming that LFHL resulted from the masking effect of PT. Additionally, improvement of LFHL after neck compression could be regarded as a positive prognostic indicator after surgery. Collectively, elimination of PT loudness and improvement of LFHL with manual compression over the ipsilateral neck may suggest the venous origin of the PT and predict a favorable outcome following repair of SS-Deh/SS-Div.